Key determinants of budget execution with the political market approach: A case study of Korean local government - Taeseop Yoon; Sungkyu Jang; Junki Lee (Global Business & Finance Review (GBFR), 2023)
Purpose: This study is aims to analyze relationships among population, resident income, fiscal characteristics, and operating expenses in Korean local governments through investigating factors that affect operating expenses for managing local governments. Design/methodology/approach: To examine the factors affecting operating expenses, this study utilizes research framework using key determinants of budget execution in terms of operating expenses with the political market approach. For doing so, this study conducts panel regression analysis using 226 Korean local governments' empirical data during FY2016-FY2020. Findings: Analytical results show that population and fiscal factors of local governments do not explain a size of operating expenses; moreover, it reveals that local governments with a small population and fiscal size tend to spend more operating expenses. Research limitations/implications: Tis study is initiated based on the hypothesis that decrease of population would lead to decline demands for public goods and public services, which reduce the number of public goods and public services, and it would finally cause the reduction of local governments' operating expenses. However, this study has a limitation regarding to restricting the period of data since FY2016. Originality/value: Despite the above limitation, this study reveals that population variables and fiscal variables do not explain a size of operating expenses of Korean local governments. Rather, the analytical result shows that local governments with a small population and fiscal size spend more operating expenses. Therefore, this study suggests that it pays more attention to improving efficiency of organizational operation of local governments in the future.
Keywords: 650; Budget execution; Operating expenses; Panel data analysis; Political market approach